Sozioökonomische Determinanten extremistischer Wahlerfolge in Deutschland: Das Beispiel der Europawahlen 1994 und 1999 - Ralph Rotte; Martin Steininger (Institute for the Study of Labor (IZA), 2000)
Empirical research on the determinants of right and left-wing extremist election successes is still dominated by descriptive statistical methods. The existing literature in political economy and political science mainly relies on interviews and survey results as well as on qualitative analyses of party organizations and programs. Contrary to this approach, in this study we try to identify significant, structural socio-economic factors which determined the vote for the right-wing ?Republikaner? party and the left-wing Party of Democratic Socialism (PDS) in the two recent elections of the European Parliament in Germany. We use a new data set on the level of German counties (Kreise) that is analyzed econometrically by a FGLS random effects panel model. The results we obtain are partly in stark contrast to empirical findings discussed in the mainstream literature and in the public. The resulting, most important areas of political action against extremist parties seem to be education, a differentiated labor market policy, social work with adolescents, and the maintenance of a generous system of social security and welfare.
Keywords: D72; I28; J60; D60; P16; 330; Elections; political extremism; labor market policy; welfare policy; Radikalismus; Wahlverhalten; Sozialökonomik; Bildungspolitik; Arbeitsmarktpolitik; Sozialpolitik; Deutschland